Influence of Estimated Training Status on Anti and Pro-Oxidant Activity, Nitrite Concentration, and Blood Pressure in Middle-Aged and Older Women - Jacomini, André M.; Dias, Danielle da Silva; Brito, Janaina de Oliveira; Silva, Roberta F. da; Monteiro, Henrique L.; Llesuy, Susana; De Angelis, Kátia; Amaral, Sandra L.; Zago, Anderson S. (Frontiers in Physiology, 2017)
The purpose of this study was to compare the association between anti and pro-oxidant activity, nitrite concentration, and blood pressure (BP) in middle-aged and older women with different levels of estimated training status (TS).The sample consisted of 155females (50-84 years) who were submitted to a physical examination to evaluate estimated TS through the “Functional Fitness Battery Test”, BP measurements, and plasma blood samples to evaluate pro-oxidant and antioxidant activity and nitrite concentrations. Participants were separated by age into a middle-aged group (<65 years) and an older (≥ 65 years) group and then subdivided in each group according to TS. Blood biochemistry was similar between groups. On the other hand, protein oxidation was lower in participants with higher TS, independent of age. Older females with higher TS presented higher nitrite concentrations, lower lipoperoxidation, and lower values of BP compared with those with lower TS. Lower GPx activity was observed in participants with higher TS compared with middle-aged with lower TS. Thus, our results suggest that good levels of TS may be associated with lower oxidative stress and higher nitrite concentration and may contribute to maintain normal or reduced blood pressure values.